District Level Geospatial Analysis of Utilization of ICDS Services Among Children in India - Kumar, Pradeep; Kundu, Sampurna; Bawankule, Rahul (Frontiers in Public Health, 2022)
Introduction: Integrated Child Developmental Services (ICDS) is the most extensive government-run health program for children with its foot spread across the complete Indian Territory. ICDS Scheme, has been provided for 40 years and has been successful in some ways. The program in reducing the undernourishment among children over the past decade has been modest and slow in India than what has been reached in other countries with comparable socio-economic measure. Therefore, this study aims to identify the district level clustering of the non-utilization of ICDS services in India, and the present research also tried relating it with socio-economic and demographic factors. Methods: The data from the fourth round of the National Family Health Survey (NFHS-4) conducted in 2015-16 in India is used to carry out the analysis. We classified the country in 640 districts and employed geospatial techniques like Moran’s I, univariate and bivariate local indicators of spatial association (LISA), and spatial error regression. Results: The non-utilization under ICDS scheme varied between 93% in West Siang district of Arunachal Pradesh and around 7% in the Kandhamal district of Odisha in 2015-16 in India. The univariate LISA results suggest striking geographic clustering of non-utilization of ICDS services among children in India (Moran’s I: 0.612). On another hand, there were regions with substantially low-low clustering of non-utilization of ICDS services in southeast India, including districts in Andhra Pradesh, Chhattisgarh, Southern Madhya Pradesh, Odisha, Telangana, and West Bengal. The findings also suggest that the proportion of the rural population (-0.190), and poor households (-0.132) in the district were significantly and negatively related while the proportion of uneducated women (0.450) was positively related to the non-utilization of ICDS services within the district. Conclusion: This is the first-ever study that examined the complex interplay of the rural population, female illiteracy, poverty, SC/ST population, and Hindu population with non-utilization of ICDS services among children in the district in India. The study highlights the inter-district geographical disparities in the non-utilization of ICDS services. Further, it confirms that underprivileged districts in terms of the rural population and poor households are also disadvantageous in the utilization of ICDS services.